Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3839/jabc.2021.060
|View full text |Cite
|
Sign up to set email alerts
|

Linarin enhances melanogenesis in B16F10 cells via MAPK and PI3K/AKT signaling pathways

Abstract: In this study, we discovered for the first time that linarin, a flavonoid compound, enhances melanin biosynthesis in B16F10 cells, and subsequently elucidated the underlying mechanism of linarin-induced melanogenesis. Linarin showed no cytotoxicity at a concentration of 42 μM and significantly increased intracellular tyrosinase activity and melanin content in B16F10 cells. Mechanistic analysis showed that linarin increased the expression of tyrosinase, tyrosinase-related protein 1 (TRP-1), and microphthalmia-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%